Commentary to the judgment of the Polish Supreme Administrative Court of 6th June 2018, II FSK 1525/16 - Artur Janicki (Prawo Budżetowe Państwa i Samorządu)
In this study the Author critically analyses the judgment of the Polish Supreme Administrative Court of 6th June 2018, II FSK 1525/16. The commented decision concerned the determination of a tax base in case of the inheritance and gift tax. The Court stated that this tax base is reduced, if a donee performs the donor’s instructions. The application of this rule is independent from the fact that a third person or the donee benefited from the instruction. The Author examines adequate provisions of Polish law on inheritance and gift tax, and he reflects the appropriate legal doctrine and court jurisdiction in this regard.